2011
DOI: 10.1007/s11434-011-4536-6
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum isotopic composition as a tracer for low-medium temperature hydrothermal ore-forming systems: A case study on the Dajiangping pyrite deposit, western Guangdong Province, China

Abstract: Little is known about the range or controls on the molybdenum isotopic composition of low-medium temperature hydrothermal ore-forming systems. We present molybdenum isotope data from 12 hydrothermal syndepositional silicalite and carbonaceous slate samples from the Dajiangping pyrite deposit in western Guangdong Province, South China. The δ 97/95 Mo values from Orebody III range from −0.02‰ to 0.29‰, with an average of 0.18‰. In contrast, the composition values from Orebody IV display a larger variation from −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Molybdenum isotope studies point to the importance of redox reactions on the δ 98 Mo of Mobearing mineral phases in low-temperature systems (Ryb et al, 2009;Greber et al, 2011;Song et al, 2011). In a Pliocene low-temperature system (100-160°C) in Switzerland, molybdate may have been transported by oxidizing surface waters into brecciated rocks (Grimsel breccia) where it was reduced, leading to precipitation of Mo-bearing sulfide phases (Greber et al, 2011; the mineralogy could not be identified by the authors).…”
Section: Ore Depositsmentioning
confidence: 98%
See 1 more Smart Citation
“…Molybdenum isotope studies point to the importance of redox reactions on the δ 98 Mo of Mobearing mineral phases in low-temperature systems (Ryb et al, 2009;Greber et al, 2011;Song et al, 2011). In a Pliocene low-temperature system (100-160°C) in Switzerland, molybdate may have been transported by oxidizing surface waters into brecciated rocks (Grimsel breccia) where it was reduced, leading to precipitation of Mo-bearing sulfide phases (Greber et al, 2011; the mineralogy could not be identified by the authors).…”
Section: Ore Depositsmentioning
confidence: 98%
“…The larger Mo isotope variation of ~3‰ in the brecciated rocks compared with individual high-temperature systems may reflect a combination of lower temperature crystallization, reduction of MoO4 2-(an uncommon species in high-temperature systems), and multiple stages of re-dissolution and re-precipitation of Mo (Greber et al, 2011). Variable redox conditions and depositional environments (open marine versus restricted) were invoked to explain the range of Mo isotope compositions in the different orebodies of the Dajiangping pyrite deposit in China (Song et al, 2011).…”
Section: Ore Depositsmentioning
confidence: 99%
“…To assess uranium resources in a rational and comprehensive way, the clarification of oreforming mechanism of uranium is an important topics that requires deeply investigation [8]. Ore-forming process is generally linked to crystal fractionation, sedimentation, metamorphism, weathering and adsorption etc [9][10][11]. However, many aspects of the mineralization processes of uranium in China remain unresolved, and the effect of adsorption is one of the crucial problems pressing for solution.…”
Section: Introductionmentioning
confidence: 99%